2016
DOI: 10.1016/j.celrep.2016.10.004
|View full text |Cite
|
Sign up to set email alerts
|

α/β-Hydrolase Domain 6 in the Ventromedial Hypothalamus Controls Energy Metabolism Flexibility

Abstract: α/β-Hydrolase domain 6 (ABHD6) is a monoacylglycerol hydrolase that degrades the endocannabinoid 2-arachidonoylglycerol (2-AG). Although complete or peripheral ABHD6 loss of function is protective against diet-induced obesity and insulin resistance, the role of ABHD6 in the central control of energy balance is unknown. Using a viral-mediated knockout approach, targeted endocannabinoid measures, and pharmacology, we discovered that mice lacking ABHD6 from neurons of the ventromedial hypothalamus (VMH) have high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 25 publications
0
28
0
Order By: Relevance
“…Expression of ACBP was partially restored in ARC astrocytes of KO-ARC ACBP mice as compared with KO-ARC GFP mice, but not in ependymocytes and tanycytes ( Figure 2B). This partial rescue of acbp in the ARC ( Figure 2C) prevented the decrease in associated virus (AAV) to rescue ACBP expression selectively in GFAP + astrocytes of the ARC of ACBP GFAP KO mice (KO-ARC ACBP ) (38). Control mice (GFAP Cre and ACBP GFAP KO) were injected with a GFP-expressing AAV ( Figure 2, A and B) (WT-ARC GFP and KO- agrp (E) mRNA levels in ARC microdissections.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Expression of ACBP was partially restored in ARC astrocytes of KO-ARC ACBP mice as compared with KO-ARC GFP mice, but not in ependymocytes and tanycytes ( Figure 2B). This partial rescue of acbp in the ARC ( Figure 2C) prevented the decrease in associated virus (AAV) to rescue ACBP expression selectively in GFAP + astrocytes of the ARC of ACBP GFAP KO mice (KO-ARC ACBP ) (38). Control mice (GFAP Cre and ACBP GFAP KO) were injected with a GFP-expressing AAV ( Figure 2, A and B) (WT-ARC GFP and KO- agrp (E) mRNA levels in ARC microdissections.…”
Section: Resultsmentioning
confidence: 97%
“…Astrocyte-specific overexpression of ACBP Ten-to twelve-week-old male C57BL/6J WT mice were injected bilaterally in the arcuate nucleus (ARC) as previously described (38) according to stereotaxic coordinates (from bregma: -1.5 mm anteroposterior, 0.15 mm lateral, and -5.9 mm dorsoventral from the dura) with 400 nl per side of either control [AAV5-GFAP(0.7)-GFP, Vector Biolabs] or overexpressor [AAV5-GFAP(0.7)-mACBP-IRES-GFP-WPRE, Vector Biolabs] virus at a concentration of 2.6 × 10 9 genome copies (GC)/μl (1.04 × 10 9 GC per side) to generate WT-ARC GFP and WT-ARC ACBP mice. Mice were allowed to recover for 1 week before the beginning of the study.…”
Section: Discussionmentioning
confidence: 99%
“…For example, degradation of the eCB 2-arachidonoylglycerol (2-AG) into arachidonic acid and glycerol is basically controlled by three different serine hydrolases: while monoacylglycerol lipase (MAGL) accounts for 85% of 2-AG degradation, alpha/beta-hydrolase domain containing (ABHD) 6, and 12 are responsible for hydrolysis of 5 and 10%, respectively (Savinainen et al, 2012). Indeed, it was shown that knockdown of ABHD6 in the ventromedial hypothalamus resulted in locally elevated 2-AG levels, finally resulting in a blunted fasting-induced feeding response and in a general diminished efficacy of the mice in order to adapt to other metabolic shifts (Fisette et al, 2016). …”
Section: Besides Cb1: Does the Ecs Provide Other Relevant Target Molementioning
confidence: 99%
“…The role of ABHD6 in the central control of energy homeostasis is an interesting topic in view that the enzyme controls 2‐AG levels. Using a viral‐mediated knockout approach and pharmacology, the Fulton and Alquier team in collaboration with us recently reported that mice lacking ABHD6 in ventromedial hypothalamic (VMH) neurons have higher VMH 2‐AG levels in conditions of endocannabinoid recruitment and fail to adapt to various metabolic challenges . These mice with VMH ABHD6 deficiency were characterized by an impaired feeding response to fasting, reduced cold induced thermogenesis and increased susceptibility to hypothermia, resistance to diet‐induced weight loss (transition from high fat diet to regular chow) and increased susceptibility to high fat diet‐induced obesity.…”
Section: Introductionmentioning
confidence: 99%
“…These mice with VMH ABHD6 deficiency were characterized by an impaired feeding response to fasting, reduced cold induced thermogenesis and increased susceptibility to hypothermia, resistance to diet‐induced weight loss (transition from high fat diet to regular chow) and increased susceptibility to high fat diet‐induced obesity. Thus, VMH ABHD6 appears to play key role in mediating energy metabolism flexibility because it is involved in the counter‐regulatory responses to major metabolic shifts, including fasting, nutrient excess, cold and dieting . Hence, ABHD6 is expected to play important actions in whole body energy balance via its actions in the CNS and its respective roles in various brain areas need to be defined.…”
Section: Introductionmentioning
confidence: 99%